Effect Of Benefits, Convenience, Security, And Features Services To Student Interest In Use Of Funds As E-Wallet - Panggabean, Dewi Febryanti; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
The purpose of this study is to confirm the use of an electronic wallet (also known as an "e- wallet") offered by the DANA application to make online payments. Electronic wallets are so far considered as a technology that makes transactions easy and convenient. Many people recognize the dangers associated with modern technology, especially when it comes to payments. Even though some people consider it unsafe, many consumers still believe in it and take advantage of it. Therefore, to create a comprehensive technology acceptance model, this study takes into account risk and dependency variables. Risk and trust impact how acceptable electronic payment methods are, according to empirical research.